(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
This present study comprises observations of the norms on land damage under the criminal legislation of the CIS nations, an investigation of means and outlooks to the legal regulation of land preservation in criminal legislation. The general scientific methods (logical, system, synthesis, and analysis) and specific scientific techniques are deployed to satisfy the study’s objectives. Based on the results It is concluded that not all criminal regulations only hold specific regulations preserving the land. This study makes an attempt to analyze the land damage signs, indicate the particulars of objective signs of land damage, and analyze the benefits and drawbacks of legal laws in comparison. Furthermore, It can be observe that relationships on the rational use and protection of land and guaranteeing environmental health and safety are substantial for the uninterrupted provision of the people with an adequate number of affordable and safe products in the near future.